2015
DOI: 10.1371/journal.pone.0124554
|View full text |Cite
|
Sign up to set email alerts
|

Health Providers’ Perceptions of Clinical Trials: Lessons from Ghana, Kenya and Burkina Faso

Abstract: BackgroundClinical trials conducted in Africa often require substantial investments to support trial centres and public health facilities. Trial resources could potentially generate benefits for routine health service delivery but may have unintended consequences. Strengthening ethical practice requires understanding the potential effects of trial inputs on the perceptions and practices of routine health care providers. This study explores the influence of malaria vaccine trials on health service delivery in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…J. Brock-Utne reports on his clinical research experience and highlights that “before you embark on your question you must prepare well, which will take much longer than you think” [31]. The result is further supported by literature stating that intense planning in clinical trials is particularly important in resource-limited settings [17, 26, 32]. The process map available on the global health network webpage shows that planning clinical trials is important and lengthy [33].…”
Section: Discussionmentioning
confidence: 99%
“…J. Brock-Utne reports on his clinical research experience and highlights that “before you embark on your question you must prepare well, which will take much longer than you think” [31]. The result is further supported by literature stating that intense planning in clinical trials is particularly important in resource-limited settings [17, 26, 32]. The process map available on the global health network webpage shows that planning clinical trials is important and lengthy [33].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies of malaria management across a range of countries in sub-Saharan Africa have pointed to the problem of the quality of care provided in many public health facilities, and particularly to the suboptimal practices related to medicine dispensing and patient counselling [ 19 22 ]. In such settings, the ethical requirement to ensure that clinical trial participants are provided with ‘gold standard’ care, following national guidelines, often results in significant resource inputs to participating health facilities [ 23 , 24 ]. Data from the current study, and several other trials, suggest that these inputs (e.g., increased levels of staff, better trained staff, provision of medicines) can result in trial participants (whether in the control or intervention arms) receiving a much higher standard of care than experienced under routine conditions, particularly with respect to the time spent explaining to patients or caregivers the reasons for a particular treatment and the steps required to maximize treatment effectiveness [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data from the current study, and several other trials, suggest that these inputs (e.g., increased levels of staff, better trained staff, provision of medicines) can result in trial participants (whether in the control or intervention arms) receiving a much higher standard of care than experienced under routine conditions, particularly with respect to the time spent explaining to patients or caregivers the reasons for a particular treatment and the steps required to maximize treatment effectiveness [ 25 , 26 ]. The extent of these inputs has led some commentators to label trials as short-term complex health interventions in themselves [ 24 , 27 ], influencing the provision and uptake of care and improving disease management among providers, patients and caregivers, including adherence to guideline implementation and dosing schedules [ 24 , 27 ]. In this study, the participants particularly mentioned that the trial staff had provided them with an adequate explanation of the dosing schedule, shown them how to administer treatment, observed administration of the first dose, and explained the necessity of completing all doses; information that, according to the national guidelines, should routinely be provided.…”
Section: Discussionmentioning
confidence: 99%
“…Known obstacles to achieving optimal childhood vaccination coverage include operational and logistical factors in effectively transporting, managing, and storing vaccines, vaccine supply shortages, inadequate number of health workers, sociocultural influences such as religious beliefs, and parental knowledge and normative attitudes [12]. A limited number of studies have examined barriers to vaccination uptake in Burkina Faso, especially during the second year of life (12 to 23 months of age) [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%